Pengawasan dan Keseimbangan antara DPR dan Presiden dalam Sistem Ketatanegaraan RI - M. Arsyad Mawardi (Jurnal Hukum IUS QUIA IUSTUM, 2008)
Among the goals of the 1945 constitution amendment is to create the balance among  the legislative, executive and judicative powers, and thus the check and balance function may take place. So as the proposal for enhancing the authority of the parliament members, which is according to the second amendment  hold the supervisory function as has been provided by section 20 (1).